Pengaruh Penggunaan Cermin Datar Dalam Ruang Tertutup Pada Sel Surya Silikon - Sidopekso, Satwiko; Yumanda, Vony (BERKALA FISIKA, 2010)
Efforts to optimize the electrical output of solar modules by maximizing the intensity of light that falls onto the surface of solar modules using a flat mirror (mirror room). The results obtained revealed that there is increasing output of solar modules. Value of Isc, Voc and the highest P consecutive outs in the amount of amperage 2:13; 20.483 35.34 volts and watts. While the value of Isc, Voc and the highest P out without a mirror room which was 0.78 amperes, respectively; 19.24 volts and 12 watts. Percentage increase in solar module output power can reach 64.22%, the highest efficiency solar module to the mirror room of 13.47% by using low lamp power. Â  Keywords: Solar Module; Electric Output Optimalization; Mirror RoomÂ